Fraud dalam Layanan BPJS Kesehatan : Kajian Etis dan Hukum Berdasarkan Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Fraud within the Social Insurance Administration Organization (BPJS) Kesehatan has emerged as a significant challenge, threatening the sustainability and integrity of Indonesia's National Health Insurance (JKN) program. Fraud can manifest in various forms, including false claims, misuse of participant data, and unauthorized utilization of healthcare facilities, involving participants, medical personnel, and healthcare providers alike. This phenomenon not only results in financial losses for the state but also diminishes the quality of healthcare services and public trust. This article analyzes BPJS fraud from the perspective of ethics and compliance with Law Number 17 of 2023 concerning Health. This law emphasizes the crucial principles of justice, transparency, and accountability in the provision of healthcare services. The prevention and handling of fraud are regulated by Minister of Health Regulation Number 16 of 2019, which mandates strict oversight, administrative sanctions, and the use of information technology for early detection. Furthermore, education and community involvement are key to strengthening reporting and oversight systems. Collaboration across sectors and the implementation of comprehensive policies are expected to maintain the sustainability and integrity of JKN, ultimately aiming to achieve fair and equitable healthcare services for all Indonesian citizens. Keywords: Ethics, Fraud, National Health Insurance, Social Insurance Administration Organization